The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0102-311x2004000200009
|View full text |Cite
|
Sign up to set email alerts
|

Vinte e quatro meses de heterocontrole da fluoretação das águas de abastecimento público de Pelotas, Rio Grande do Sul, Brasil

Abstract: The aim of the present study was monthly evaluation of fluoride levels in the public water supply in Pelotas, Rio Grande do Sul State, Brazil, and the validity of forming external control groups. Pelotas was divided into 16 geographic regions, including the three public water treatment stations. Water samples were collected from November 1999 to October 2001. Two samples were drawn from each region. Samples were sent to the Fluoride Health Surveillance Laboratory at Universidade do Vale do Itajaí. Fluoride ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
17

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 19 publications
0
13
0
17
Order By: Relevance
“…This temporal increase in the proportion of water samples with appropriate fluoride levels demonstrates the importance of longitudinal studies and the effectiveness of constant monitoring, which facilitates the operational control of water fluoridation procedures and improves the quality of public water supplies. [19][20][21][22][23] In another study of eight cities in northwestern São Paulo State conducted during a 36-month period from November 2004 to October 2007, Saliba et al 24 found a higher proportion (77.4%) of water samples with fluoride levels within recommended parameters. However, it should be noted that these eight cities used a single water source.…”
Section: Discussionmentioning
confidence: 99%
“…This temporal increase in the proportion of water samples with appropriate fluoride levels demonstrates the importance of longitudinal studies and the effectiveness of constant monitoring, which facilitates the operational control of water fluoridation procedures and improves the quality of public water supplies. [19][20][21][22][23] In another study of eight cities in northwestern São Paulo State conducted during a 36-month period from November 2004 to October 2007, Saliba et al 24 found a higher proportion (77.4%) of water samples with fluoride levels within recommended parameters. However, it should be noted that these eight cities used a single water source.…”
Section: Discussionmentioning
confidence: 99%
“…Todos os estudos citados mostraram variação na adequação da concentração de flúor ao longo do tempo e dos pontos de coleta, e elevada proporção de concentrações consideradas inadequadas em sua maioria 12,14,15,17,21,22,23,24,26 . Evidenciam-se, assim, dificuldades operacionais na manutenção adequada da concentração ótima de flúor nas águas de abastecimento público no contexto brasileiro, justificando a necessidade e importância da instituição e manutenção de sistema de vigilância sanitária da fluoretação das águas de abastecimento públi-co. Em acréscimo, problemas legais contribuem para tal situação.…”
Section: Discussionunclassified
“…Entre elas: as normas do Laboratório de Vigilância do Flúor da UNIVALI, que foram utilizadas em Chapecó e também em outros estudos 23,26 ; a Portaria nº. 518 30 , que estabelece um ponto de coleta para cada 10 mil habitantes 18 ; e a distribuição por região administrativa e geográfica 12,15,16,17,27 .…”
Section: Discussionunclassified
“…Na Tabela 1, constata-se que a maioria das amostras não atingiu a faixa aceitável (0,60 a 20 apresenta resultado semelhante em Niterói, Rio de Janeiro. Falhas do controle da fluoretação tem sido verificada por estudos tanto no Nordeste como em outras regiões do país 21,22,23,24,25 . A situação observada na cidade de São Paulo é diferente pois das amostras examinadas, 93% estavam com concentração de flúor em níveis considerados ótimos 12 .…”
Section: Discussionunclassified